2021
DOI: 10.3390/bdcc5030042
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Localization for Personalized Ambient Assisted Living of Multiple Users in Multi-Floor Smart Environments

Abstract: This paper presents a multifunctional interdisciplinary framework that makes four scientific contributions towards the development of personalized ambient assisted living (AAL), with a specific focus to address the different and dynamic needs of the diverse aging population in the future of smart living environments. First, it presents a probabilistic reasoning-based mathematical approach to model all possible forms of user interactions for any activity arising from user diversity of multiple users in such env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Using Google Trends, Ortiz-Martínez et al [68] showed that there was a high correlation between the COVID-19 incidence in Colombia and Google searches on COVID-19 in Colombia (R 2 = 0.8728 and p < 0.0001). In addition to the above, in the last few years, Google Trends has also had a wide range of interdisciplinary applications related to the understanding and analysis of public health concerns [69][70][71], societal problems [72][73][74], emerging technologies [75][76][77], human behavior analysis [78][79][80][81], assistive technologies [82][83][84][85], humanitarian issues [86][87][88][89], and smart technologies [90][91][92][93]. Therefore, it may be concluded that prior works in this field have focused on using Google Trends related to mining, analysis, and investigation of multimodal components of web behavior for a wide range of applications and use cases, with a specific focus on studying and analyzing web behavior during various virus outbreaks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using Google Trends, Ortiz-Martínez et al [68] showed that there was a high correlation between the COVID-19 incidence in Colombia and Google searches on COVID-19 in Colombia (R 2 = 0.8728 and p < 0.0001). In addition to the above, in the last few years, Google Trends has also had a wide range of interdisciplinary applications related to the understanding and analysis of public health concerns [69][70][71], societal problems [72][73][74], emerging technologies [75][76][77], human behavior analysis [78][79][80][81], assistive technologies [82][83][84][85], humanitarian issues [86][87][88][89], and smart technologies [90][91][92][93]. Therefore, it may be concluded that prior works in this field have focused on using Google Trends related to mining, analysis, and investigation of multimodal components of web behavior for a wide range of applications and use cases, with a specific focus on studying and analyzing web behavior during various virus outbreaks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Having all of the world in their pockets, or more precisely in their hands, people are the centre for some cultural informatics approaches. Customization, personalization, personality of the people are only some of the "keywords" that lead to this change of stance towards people [71][72][73]. The museum is not just an information carrier, the object is not only a masterpiece, the work from curators and guides is not only static, but we are designing experiences and their maximization, brain stimulation, immersion of different levels, and total adaptation to the needs of the visitors.…”
Section: Adaptation On Peoplementioning
confidence: 99%
“…Due to the behavior of various rates of reduction in the mental, emotional, social, motor, and psychological skills and more obstacles such as behavioral, neurological disorders, disabilities, cognitive, and visual impairments, depending on the diversity, the aging population is corresponding with multiple and various effects on the older people (Correia et al, 2021). The population of aging people in the world is increasing, and the population of caregivers is decreasing in looking after older people, which creates several difficulties (Thakur and Han, 2021).…”
Section: Introductionmentioning
confidence: 99%